Taxonomy of Clostridium bifermentans and Clostridium sordellii III. Agglutinability of Heat-Resistant Substrains of Clostridium sordellii - Huang, C. T. (1965)
Huang, C. T. (Kanazawa University, Kanazawa, Japan), Kenzo Tamai, and Shoki Nishida. Taxonomy of Clostridium bifermentans and Clostridium sordellii, III. Agglutinability of heat-resistant substrains of Clostridium sordellii. J. Bacteriol. 90:391–394. 1965.—By cross-agglutination tests with Clostridium bifermentans and C. sordellii antisera, the heat-resistant substrains from each pathogenic strain of C. sordellii were found to possess antigens of C. bifermentans in addition to displaying changes in biological activities. The agglutinability and biological activities varied with the sporulating potency acquired. Agglutinin-absorption tests further proved that heat-resistant substrains of C. sordellii were immunologically identical to C. bifermentans.